Influence of torque flow, pressure on the performance of a fire pump at the gas complex level - Benmoussa, Moufida; Inel, Fouad (Edelweiss Applied Science and Technology, 2024)
In recent years, motor pumps have played an increasingly important role in transferring fluids by increasing pressure, such as in power plants, hydrocarbon complexes and oil companies. Although these companies have advantages, their lack of maintenance can negatively impact their production, resulting in wasted costs and time, as well as putting human lives at risk. Restoration and modernization with improper maintenance or wrong policies can lead to critical and dangerous situations for equipment, the environment and people. And in this sense, we will be interested in the problem of protection against a fire in a gas installation; with the aim of carrying out a performance test of the electric pump which aims to evaluate the performance of the pump of the firefighting network of the gas complex. To achieve our objective according to the NFPA 20 Standard we have the following approach: Verification of measuring instruments. Installation of an ultrasonic flow meter. Application of the performance test on the fire pump. Controls flow according to pressure. Projection of the results obtained on the manufacturer's performance curve. The comparison between the manufacturer's performance curve and the performance curve obtained. Analysis of the results obtained. Finally, to monitor pump performance, we recommend the immediate installation of a permanent flow meter at the pump discharge level and avoid any type of risk.